Participatory plant breeding and property rights - CGIAR Systemwide Program on Participatory Research and Gender Analysis for Technology Development and Institutional Innovation (CGIAR Systemwide Program on Participatory Research and Gender Analysis for Technology Development and Institutional Innovation, 2001)
Participatory plant-breeding (PPB) efforts have proliferated within the last 10 years; however, other key aspects have yet to be explored, As in many other fields, the property rights and ethical issues of participatory plant breeding are lagging far behind technical advances, The urgency to define property-rights issues for PPB arises al an opportune time, This paper introduces incipient work (including development of a state-of-the-art paper) on property rights (Le., legal ¡issues, best-practice options to guide field programs, and ethical concerts in PPB work) and participatory plant breeding, Steps for development of the state-of-the-art paper and the types and issues lo be covered are listed.